(untitled) (Indian Journal of Public Health Research & Development, 2024)
Background: In the rural regions of Telangana State, many women are actively involved in the occupation of beedi rolling. Cigarette smoke either active or passive exerts deleterious effects on reproductive organs and function by means of both direct toxic influences, termed ovotoxicity, and the reduction of hormone secretion. Methods: The study involved a cohort of 320 women employed as beedi rollers and 280 women with no occupational exposure to chemicals for comparison. Serum samples were used to estimate the levels of Estrogen, Progesterone, Testosterone, Follicle Stimulating Hormone, luteinizing hormone, T3, T4 and TSH using Sandwich and competitive ELISA methods. Conclusion: The findings of the current study unveiled compelling statistical significance in the levels of estrogen, progesterone, luteinizing hormone (LH), follicle-stimulating hormone (FSH), T3 and T4. In conclusion, our study reveals a noteworthy correlation between beedi rolling and alterations in hormonal profiles of rural women in Telangana.